Die politische Metapher »links« und die politischen Orientierungen von Studierenden (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 1996)
On the basis of a survey on political views among students at universities in Hesse, the author shows that the assertion, that the left-right-dichotomy has lost empirical or theoretical evidence cannot be maintained. They belong to the symbolical order of modern politics as floating significants, although their meaning is changing at the moment.
Keywords: Universität; Krise; Links; Rechts; politische Orientierung